Teoría y práctica del cine "nacional" en la guerra civil española - Lénárt, András (Acta Hispanica, 2011)
The insurgent army of the Spanish extreme right took advantage of the power of cinema, just likeother European leaders did in the 20Th centuiy. Between 1936 and 1939 (and during the wholeregime as well) Spanish screens were spread with nationalist visual propaganda in order to shape thecourse of public opinion and to implant the ideology of the Falangist Movement in the citizens. GeneralFranco, his confidants and even his relatives exercised tight control over film politics, giving preference toshort films, documentaries and newsreels. In this essay we examine the theoretical and industrialbackground of the incipient francoist film politics during the Civil War and we highlight some of themost important products of this effort , briefly touching upon a few relevant international matters, suchas the anti-Franco movement of Hollywood or the German and Italian support.